PREVALENCE OF CHRONIC PERIAPICAL LESIONS IN DIABETIC VERSUS NON-DIABETIC PATIENTS: A RETROSPECTIVE STUDY - Cristi Giuroiu; Anca Melian; Claudiu Topoliceanu; Cristina Dascalu; Andreea Frumuzache; Mihaela Salceanu (Romanian Journal of Oral Rehabilitation)
Aim. The aim of study was to. evaluate the relationship between glycemic control and the presence of chronic apical periodontitis CAP in endodontically treated teeth among patients with type 2 diabetes, by comparing with those of a non-diabetic control group and analyzing differences according to sex and place of residence. Materials and method. This retrospective study evaluated the endodontic status of 90 patients with type 2 diabetes (mean age 60.13 years). All patients underwent fasting blood glucose and HbA1c testing, and data were collected regarding the number and location of endodontically treated teeth, both with and without chronic apical periodontitis (CAP). The prevalence and distribution of CAP were analyzed in relation to socio-demographic variables and compared to a non-diabetic control group, using descriptive and comparative statistical methods. Results.. Mean glycemia was 201.44 mg/dL in diabetic patients and 90.72 mg/dL in non-diabetic patients. The steepest glycemia increases were observed in female diabetic patients, with values rising from 207.47 mg/dL (0–1 teeth without CAP) to 382 mg/dL (≥ 4 teeth), and in urban diabetic patients, where glycemia increased from 179.43 mg/dL to 330 mg/dL; non-diabetic individuals maintained stable glycemia levels across all subgroups, with values generally ranging between 84.67 and 96.14 mg/dL. Conclusions. Glycemia levels were significantly higher and more variable in diabetic patients compared to non-diabetics, particularly as the number of endodontically treated teeth increased, with or without chronic apical periodontitis. The steepest rises were observed in female and urban diabetics, while non-diabetics maintained stable glycemia values across all subgroups.